Polyphenolic Content, Antioxidant and Antimicrobial Activity of Hydrosols from Some Aromatic Lamiaceae Plants - Alexandra Gaspar-Pintiliescu; Elena Mihai; Ana-Maria Stanciuc; Ruxandra Elena Anton; Adriana Florina Popescu; Oana Craciunescu (Proceedings, 2020)
Hydrosols, also named hydrolates or aromatic waters, are considered distillation by-products obtained during essential oil extraction from herbs or spices, which are usually discarded. [...]